11.6k views
6 votes
5-(6- 9x)=1-(4-10 ) please​

User ZhaoGang
by
6.0k points

1 Answer

3 votes


\qquad\qquad\huge\underline{{\sf Answer}}♨

Let's solve ~


\qquad \sf  \dashrightarrow \:5 - ( 6 - 9x) = 1 - (4 - 10)


\qquad \sf  \dashrightarrow \:5 - 6 + 9x = 1 - 4 + 10


\qquad \sf  \dashrightarrow \: 9x - 1 = 7


\qquad \sf  \dashrightarrow \:9x = 8


\qquad \sf  \dashrightarrow \:x = (8)/(9)

User Artem Tutov
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.